SOME METHODOLOGICAL ISSUES OF DEVELOPMENTAL LEARNING - Buryak, V.K. (Pedagogy of Higher and Secondary Education, 2009)
L. Vygotsky’s statements concerning the formation of personal powers qualities and abilities of a human individual that arise from one’s real social conditions have been examined at the new level in the article.